A Novel Approach for Fabricating LaMnO3 Thin Films Using Combined Microwave Combustion and Pulsed Electron Deposition Techniques. (4th March 2019) - Tran, Thi Ha; Tang, Thi Trung Anh; Pham, Nguyen Hai; Bach, Thanh Cong; Sai, Cong Doanh; Nguyen, Quang Hoa; Le, Van Vu; Nguyen, Hoang Nam; Doan, Quoc Khoa; Nguyen, Trong Tam; Le, Viet Bau; Ho, Khac Hieu; et al.
Abstract : LaMnO3 (LMO) nanopowder was synthesized by the microwave combustion method using glycine and nitrate salts of La and Mn as precursors. The as-prepared LMO powder was pressed at high pressure and annealed at 1000°C for 8 hours to make a target for thin film deposition. The structural and elemental analysis was obtained by X-ray diffraction (XRD) and energy dispersive X-ray spectroscopy (EDS). Thin films of LMO were fabricated using pulsed electron deposition (PED) at room temperature. The effects of discharge voltage and oxygen/argon flux ratio on the produced thin films were studied. The study shows that stoichiometry and structure of the target was preserved well in the thin films prepared with a discharge voltage from 14 to 15 kV, while the oxygen/nitrogen flux ratio did not show a clear effect on the quality of thin films.